TRANSFORMING EDUCATION TO UNLOCK LIFELONG OPPORTUNITY AND SUCCESS MINDSET THROUGH WOMEN’S LEADERSHIP - Yulia Rahmi Ilmani (Managere: Indonesian Journal of Educational Management, 2023)
This research aims to understand women's leadership in educational transformation through women leaders in educational institutions. With this evidence, women get equal opportunities to receive education and become leaders. In Situbondo there are many female leaders, one of the most prominent being the Deputy Regent of Situbondo who is also the Chair of the Situbondo Muslimat. The female leader who was deputy to be regent was the first time in Situbondo who was also the leader of the Miftahul Ulum Besuki Islamic Boarding School. The approach used in this research is qualitative with a case study type. Data obtained through observation, in-depth interviews, and documentation. The data collected was analyzed using the Miles and Huberman data analysis technique, which consists of data reduction, data display and verification. The research results show that women's leadership in educational transformation which can build mindsets is carried out in the form of example, providing rewards, paying attention to subordinates who have problems, and providing soft skills training.